Effect of bath ionic strength on adhesion and tribological properties of pure nickel and Ni-based nanocomposite coatings. Issue 6 (18th March 2016) - Bajwa, Rizwan Sarwar; Khan, Zulfiqar; Bakolas, Vasilios; Braun, Wolfgang
Abstract: The effect of electrolytic chemical concentration on wear-resistance, corrosion-resistance, adhesion and wettability properties of pure nickel and nickel–alumina composite coatings has been investigated in this paper. Coatings were electroplated over steel substrates under constant pulse conditions using pulse electrodeposition technique. Corrosion-resistance results show that the anti-corrosion properties are increasing with medium concentration (MC) both for pure nickel and nickel–alumina composite coating. For anti-wear properties, the MC showed increasing trend in case of pure nickel coatings but decreased in nickel–alumina composite coatings. In composite coating, the higher and low concentrations of electrolyte showed the higher wear resistance properties. Furthermore, the influence of electrolyte concentration on changing surface morphologies, mechanical, wettability and adhesion properties have been investigated and reported here. Surface morphologies of the synthesized coatings were studied with scanning electron microscopy (SEM) and energy-dispersive spectroscopy. Coatings surface mapping and wear analyses were examined by using 3D white light interferometry.